The Role of Artificial Intelligence in Civil Engineering Applications and Programs - Alghurair, Mohsen Saud; Fahim, Ayman Rushdy (Journal of engineering sciences and information technology, 2023)
The integration of artificial intelligence (AI) techniques in civil engineering programs and drawing techniques has the potential to revolutionize the industry. This study explores the benefits, challenges, and strategies for the effective utilization of AI in civil engineering. The research investigates the current state of AI integration, examines its applications in structural analysis, design, documentation, and project management, and identifies the barriers hindering widespread adoption. The study highlights the importance of data-driven decision-making, enhanced design visualization, improved accuracy and efficiency, streamlined documentation and communication, and enhanced project management and control. By addressing the challenges and providing insights into AI techniques, this study aims to bridge the gap between theoretical potential and practical implementation, paving the way for more sustainable and intelligent civil engineering projects.